How Much Is Enough? Examining Computer Science and Civil Engineering Citation Data to Inform Collection Development and Retention Decisions in Three Large Canadian University Libraries. - Michelle Spence; Tara Mawhinney; Eugene Barsky (Issues in Science and Technology Librarianship, 2012)
Science and engineering libraries have an important role to play in preserving the intellectual content in research areas of the departments they serve. This study employs bibliographic data from the Web of Science database to examine how much research material is required to cover 90% of faculty citations in civil engineering and computer science. Bearing in mind the importance of access to current as well as past research, as well as the issue of space in libraries, the study evaluates citations from one year's worth of research output from faculty in three prominent Canadian universities with departments in civil engineering and computer science: University of Toronto, University of British Columbia and McGill University for the purpose of best aligning collection development activities with science and engineering research needs. The findings for all three institutions combined show that 25 years of computer science literature is needed to cover 90% of researchers' citations, whereas 30 years of materials are needed for civil engineering. We also found that the citation data is not only discipline specific, but also location specific, and a one-size-fits-all approach is not appropriate when making collections and retention decisions. [ABSTRACT FROM AUTHOR]